2018
DOI: 10.30880/jst.2018.10.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Polyvinyl Alcohol/Chitosan Hydrogel Loaded with Fertilizer Compound: Preparation, Properties and Effect on Seed Germination

Abstract: This work reports the reinforcement of polyvinyl alcohol (PVA) hydrogel with chitosan as potential superabsorbent (SAP) fertilizer. The PVA/Chitosan hydrogel was prepared using superficial freeze thawing method. Mechanical properties and swelling ratio of the SAP hydrogels were optimum at 6 wt% of chitosan loading. Morphological analysis of the PVA/Chitosan hydrogel revealed excellent crystal like structure distribution and smooth of the surface due to good compatibility between the materials. The water retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The authors also evaluated the potassium release behavior of both hydrogels in soil, and determined that CS hydrogels exhibited higher cumulative release of potassium (63% after 30 days). Similar studies regarding PVA/CS hydrogels crosslinked with GA were carried out by Nayan et al [ 39 ], who prepared these materials using a superficial freeze-thawing method ( Table 1 , entry 7). Optimal mechanical properties and the best swelling ratio of the hydrogels were obtained at 6 wt.% CS loading, and these hydrogels achieved moderate water absorbency (0.58 g/g in phosphate buffered saline (PBS) solution) and water retention in the soil (48% after 15 days).…”
Section: Strategies For Fabricating Cs Hydrogels and Their Potentimentioning
confidence: 65%
See 1 more Smart Citation
“…The authors also evaluated the potassium release behavior of both hydrogels in soil, and determined that CS hydrogels exhibited higher cumulative release of potassium (63% after 30 days). Similar studies regarding PVA/CS hydrogels crosslinked with GA were carried out by Nayan et al [ 39 ], who prepared these materials using a superficial freeze-thawing method ( Table 1 , entry 7). Optimal mechanical properties and the best swelling ratio of the hydrogels were obtained at 6 wt.% CS loading, and these hydrogels achieved moderate water absorbency (0.58 g/g in phosphate buffered saline (PBS) solution) and water retention in the soil (48% after 15 days).…”
Section: Strategies For Fabricating Cs Hydrogels and Their Potentimentioning
confidence: 65%
“…Aldehydes are common cross-linking agents that react with the amino groups in CS, forming a covalent imine bond. Several approaches have been developed for synthesizing CS-based hydrogels crosslinked with GA [ 34 , 38 , 39 , 40 , 41 ], glyoxal [ 42 ] or salicylic aldehyde [ 43 ] for potential agricultural use.…”
Section: Strategies For Fabricating Cs Hydrogels and Their Potentimentioning
confidence: 99%
“…This hydrogel could have a positive effect on the germination of okra plants and allow the controlled release of fertilizer. 35 CS based hydrogels have been prepared by mild oxidation and grafting technique. Investigation of swelling degree and water retention by both hydrogels showed that grafted hydrogel has more swelling ability than oxidized CS hydrogel.…”
Section: Chitosan Based Hydrogelsmentioning
confidence: 99%
“…Synthetic polymers like polyvinyl alcohol (PVA) have exceptional characteristics such as excellent hydrophilicity, biodegradable, and non-toxicity [ 154 ]. Despite that, PVA cannot form the outstanding hydrogel in the aspect of strength and low swelling ratio for use as fertilizer release [ 155 ]. Hence, the incorporation of other polymers with cellulose as RC hydrogel for nutrients’ reservoir is favorable as to build up the advanced properties of fertilizer release mechanism.…”
Section: The Potential Applications Of Regenerated Cellulose Products For Agriculturementioning
confidence: 99%